Globalization and Cultural Identity Dilemmas - Sebastian Andrei Labes (CES Working Papers, 2014)
This paper aims to present an important phenomenon of our world, namely the contradictory relationship between globalization and cultural identity. In this work identity is understood as a cultural practice therefore it cannot be analyzed without taking into account global communication and diversity. The multidimensional transformation of our society in the XXI century is marked by increased interconnectivity and affirmation of singular identities. These identities come in constant tension with the context in which the existing political forms that are in crisis and the restructuring processes through new projects are struggling to set up a new society. Globalization versus cultural identity it's not a zero-sum game even though the two might be perceived as opposite processes this paper argue that it globalization cultural identity can go hand in hand with globalization.
Keywords: F60; Z13; 330; globalization; cultural identity